Horror and science fiction cinema and society American culture and politics in the Cold War and after through the projector lens - Harris, Martin, (College teacher) (New York : Routledge, 2024)
Examining how horror and science fiction films from the 1950s to the present invent and explore fictional us-versus-them scenarios, this book analyzesthe differentwayssuch films employ allegory and/or satire to interrogate the causes and consequences ofincreasing polarization in American politics and society. Starting with the killer ants film with an anti-communist subtext Them! (1954) and concluding with Jordan Peele's social horror film with revenge-seeking homicidal doppelgngers Us (2019), Martin Harris highlights social and political contexts, contemporary reviews and responses, and retrospective evaluations to show how American horror and science fiction films reflect and respond to contemporary conflicts marking various periods in U.S. history from post-WWII to the present, including those concerning race, gender, class, faith, political ideology, national identity, and other elements of American society. Horror and Science Fiction Cinema and Society draws upon cinematic sociology to provide a resourceful approach to American horror and science fiction films that integrates discussion of plot construction and character development with analyses of the thematic uses of conflict, guiding readers' understanding of how filmmakers create otherworldly confrontations to deliver real-world social and political commentary.
Keywords: Motion pictures -- Social aspects -- United States; Horror films -- United States -- History and criticism; Science fiction films -- United States -- History and criticism; SOCIAL SCIENCE / Popular Culture; HISTORY / United States / 20th Century